Structure and function of rhizosphere soil microbial communities associated with root rot of Knoxia roxburghii - Liu, Chunju; Li, Heng; Dong, Jiahong; He, Xiahong; Zhang, Lei; Qiu, Bin (Frontiers in Microbiology, 2024)
The microbial communities in rhizosphere soil play important roles in plant health and crop productivity. However, the microbial community structure of rhizosphere soil still remains unclear.In this study, the composition, diversity and function of the microbial communities in the rhizosphere soil of healthy and diseased plants were compared using Illumina MiSeq high-throughput sequencing.The Sobs (richness) and Shannon (diversity) indices of the soil microbial communities were higher in the rhizospheres of 2-and 3-year-old susceptible plants than in those of the healthy plants. With the increase in planting time, the numbers of fungi tended to decrease, while those of the bacteria tended enrichment pathway of the K. roxburghii rhizosphere bacteria (p<0.05). The soil physical and chemical properties, including the pH, AK, total potassium (TK), and catalase (S_CAT), had the most significant effect on the soil fungal community, and most of the soil physical and chemical properties significantly correlated with the bacterial community. This study demonstrated that the occurrence of root rot had an important effect on the diversity, structure and composition of microbial communities. In addition, the results will provide a theoretical basis to prevent and control root rot in K. roxburghii.